2013
DOI: 10.7314/apjcp.2013.14.12.7221
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Bioinformation Analysis of the MRNA Profile of Fascin Knockdown in Esophageal Squamous Cell Carcinoma

Abstract: Background: Fascin, an actin-bundling protein forming actin bundles including filopodia and stress fibers, is overexpressed in multiple human epithelial cancers including esophageal squamous cell carcinoma (ESCC). Previously we conducted a microarray experiment to analyze fascin knockdown by RNAi in ESCC. Method: In this study, the differentially expressed genes from mRNA expression profilomg of fascin knockdown were analyzed by multiple bioinformatics methods for a comprehensive understanding of the role of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…NSCLC accounts for~80% of all lung cancer cases, which further consists of three major subtypes: squamous cell carcinoma, adenocarcinoma, and large-cell carcinoma, which are differentiated on the basis of pathological characteristics (49,54). The three most commonly applied treatment methods for NSCLC include surgery, chemotherapy, and radiotherapy (13,48). However, because of a number of side effects, including chemotherapy-induced cell death, the above treatments have a low efficacy (17).…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC accounts for~80% of all lung cancer cases, which further consists of three major subtypes: squamous cell carcinoma, adenocarcinoma, and large-cell carcinoma, which are differentiated on the basis of pathological characteristics (49,54). The three most commonly applied treatment methods for NSCLC include surgery, chemotherapy, and radiotherapy (13,48). However, because of a number of side effects, including chemotherapy-induced cell death, the above treatments have a low efficacy (17).…”
Section: Introductionmentioning
confidence: 99%
“…With the use of computational methods, numerous studies have discovered that several cancers are markedly triggered by epigenetic alterations (Mahdavi et al, 2012;Wu et al, 2013;Jiang et al, 2014;Song et al, 2014;Zhuo e t al., 2014;Wang and Yan, 2015). The present study was also an attempt to determine the in silico interaction of MIC and 1,3-dimethylurea with several domains of DNMT1.…”
Section: Discussionmentioning
confidence: 99%
“…After validating cDNA microarray data by real‐time reverse transcription polymerase chain reaction, western blot, and immunofluorescence analyses, we found that two genes, CYR61 (cysteine‐rich, angiogenic inducer 61) and CTGF (connective tissue growth factor), were downregulated through the transforming growth factor‐β signaling pathway, and were directly involved in the fascin‐mediated proliferation and invasiveness of ESCC cells . Furthermore, to comprehensively understand the mRNA profile of fascin knockdown in the ESCC cell line, EC109, and to illustrate the functional roles of fascin, we carried out multiple bioinformatics analyses for differentially expressed genes, including gene ontology enrichment and functional annotation analyses, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, promoter sequence analysis, and protein‐protein interaction sub‐network analysis . Gene ontology term enrichment found that fascin was associated with cytoskeleton organization, including cell adhesion, F‐actin filament binding, and F‐actin cytoskeleton.…”
Section: Molecular Basis Of Fascin Function In the Progression Of Esccmentioning
confidence: 95%
“…The promoter sequence analysis showed that transcription factors MNB1A, c‐ETS, GATA2 and Prrx2 potentially regulated the downregulated gene set, whereas Arnt‐Ahr, ZNF 41, Ubx and TCF11‐MafG potentially co‐regulated the upregulated gene set. The protein–protein interaction sub‐network analysis showed that differentially expressed genes interacted with other proteins directly or indirectly in multiple subcellular layers of the extracellular membrane–cytoskeleton/cytoplasm–nucleus …”
Section: Molecular Basis Of Fascin Function In the Progression Of Esccmentioning
confidence: 99%